COSMOPOLITANISM IN THE FACE OF POPULISM – CONTEMPORARY CHALLENGES ON THE PATH OF EUROPEAN IDENTITY FORMATION - Cichocki, Piotr (Society Register, 2017)
The paper examines the continuing viability of the critique of methodological nationalism in the context of recent resurgence of nationalist sentiments across western liberal democracies. Using the distinction between first and second modernity, it shows how cosmopolitan social theorising can actually be seen as predictive of some of the effects that nationalist populism has enjoyed in the context of the post-2008 series of crises. The discussion is mostly focused on the challenge the current political dynamics poses to the weak forms of social integration underpinning the project of European supra-national unification.